The Concept of Freedom in liberalism’s Thought, for Instance: Friedrich .A. Von Hayek's Vision (Raparin Journal of Humanities (RJH), 2021)
Liberalism thus views the concept of freedom as a fundamental element of its intellectual foundation and without access to and defense of freedom, there is no meaning for the existence and survival of liberals. Due to the wide range of views of liberalism and the differences of opinion of liberal thinkers and different trends, attitudes and views on different freedoms, for example some of the thinkers believe in the interference of the state power in personal freedoms with the goal of creating social justice and economic justice and so on..., such as the thinkers of the Social liberal trend in the thought of liberalism, But some other thinkers believe in the protection of individual freedoms from interfering of the power of the state, and reject any form of interference in freedom, such as thinkers of the Libertarians trend in the thought of liberalism, including (Friedrich A. von Hayek).These two views of liberalism are expressed in terms of freedom, as: positive freedom (when the state intervenes in freedoms), and negative freedom (that freedom is protected from the interference of state power).  (Hayek) rejects positive freedom and believes that any interference in the freedom, economy, and property of individuals, commodities, and markets, leads to the deterioration of the security and stability of individuals on one hand, and the creation of an oppressive, tyrannical and dictatorial power or regime on the other hand. This condition becomes the cause and means of the departure of individuals and the coexistence of the living system to slavery.